Potential association of anticholinergic medication intake and caries experience in young adults with xerostomia - Mayank Kakkar; Estela Caetano de Souza Valentim; Abdul Basir Barmak; Szilvia Arany (Elsevier, 2023)
Background/purpose: Growing prescription of anticholinergic medications has a critical effect on oral health. A link between anticholinergic medication-induced xerostomia (subjective feeling of oral dryness) and a high Decayed, Missing, and Filled teeth (DMFT) index has been reported in the older population. The purpose of this retrospective study is to determine anticholinergic exposure and prevalence of the most frequently used anticholinergic medications in adults 18-44 years of age, as well as to explore xerostomia and its association with caries status. Materials and methods: We performed a retrospective study of adults between the age of 18 and 44 years who received a dental examination between January 2019 and April 2010, at Eastman Institute for Oral Health (EIOH), Rochester, NY. We reviewed the electronic dental charts and medical records of 236 adults with xerostomia. Results: 71% of young adults with xerostomia were prescribed at least five or more medications (polypharmacy), and 85% took at least one anticholinergic drug. The average anticholinergic drug scale (ADS) was 2.93. We found systemic conditions such as cardiac, neurological, and sleep apnea affecting the DMFT index by predicting the caries status (P < 0.001). Conclusion: Anticholinergic exposure and medication-induced xerostomia in younger adults are associated with dental caries and require complex interdisciplinary therapy.